2017
DOI: 10.5530/fra.2017.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Evaluation and In vitro Antioxidant Activity of Various Solvent Extracts of Leucas aspera (Willd.) Link Leaves

Abstract: Background: Free radicals initiate the oxidative stress and damage the healthy cells. These damages contribute ageing, cancer, cardiovascular and inflammatory diseases. Phenolic compounds, flavonoids and tannins are directly contributed to antioxidant activity. Objective: The present study was attempted to evaluate the phytochemicals present in various solvent extracts obtained from Leucas aspera (Willd) Link leaves (L. aspera) and its antioxidant activity using different in-vitro models. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
(12 reference statements)
1
11
0
Order By: Relevance
“…Various study revealed that phenolic and flavonoid are the most important substance that present numerous biological activity and pharmacology properties. 31 The results of this study support that medicinal plants in NTT is rich in phenolic and flavonoids that might contribute to potential antioxidant activities. S. quadrifida is a well-known as NTT traditional medicinal plants.…”
Section: Discussionsupporting
confidence: 64%
“…Various study revealed that phenolic and flavonoid are the most important substance that present numerous biological activity and pharmacology properties. 31 The results of this study support that medicinal plants in NTT is rich in phenolic and flavonoids that might contribute to potential antioxidant activities. S. quadrifida is a well-known as NTT traditional medicinal plants.…”
Section: Discussionsupporting
confidence: 64%
“…They also suggested ethanol or isopropanol (polar solvent selection) and petroleum ether (non-polar solvent selection) for better extraction of phytochemicals and phytoconstituents. Moreover, better antioxidant activity was observed in wild leaf extracts when compared to in vitro callus extract [31].…”
Section: Antioxidant Propertymentioning
confidence: 95%
“…Antioxidant property of L. aspera was reported by many researchers. 19,20,21,22,23,24,25,26,27 The ethanolic extract of L. aspera exhibited very potent antioxidant effect. 25 Better antioxidant activity was observed in the petroleum ether extract of L. aspera leaf and the order of the activity is petroleum ether > ethanol > isopropyl alcohol > ethyl acetate > chloroform.…”
Section: Anti Oxidant Propertymentioning
confidence: 99%
“…25 Better antioxidant activity was observed in the petroleum ether extract of L. aspera leaf and the order of the activity is petroleum ether > ethanol > isopropyl alcohol > ethyl acetate > chloroform. 26 They also suggested ethyl alcohol or isopropyl alcohol (polar solvent selection) and petroleum ether (nonpolar solvent selection) for the better extraction of phytochemicals. Better antioxidant activity was observed in wild leaf extracts when compared to in vitro callus extract.…”
Section: Anti Oxidant Propertymentioning
confidence: 99%